At Last the 1948 Show Episode 1-13 - Fordyce, Ian; Cleese, John; Chapman, Graham; Feldman, Marty (bfi, 2019)
This ground-breaking, splendidly silly and surreal comedy sketch series, written and performed by John Cleese, Graham Chapman, Tim Brooke-Taylor and Marty Feldman, also starring the lovely Aimi MacDonald, was a major milestone on the road to Monty Python's Flying Circus, The Goodies and everything that came after. This lovingly curated new deluxe three-disc set restores all the existing episodes from both series of the programme in the correct order, and is as complete as is currently possible. It includes all ten surviving episodes, two almost completely reconstructed episodes, and the complete audio of a further episode with fragments of film restored; all drawn from the vaults of the BFI National Archive, and proudly presented alongside an array of newly-filmed and archive extras. [www.amazon.co.uk]